Peran Orang Tua Dalam Mendidik Anak-Anak Melalui Pekerjaan Rumah Tangga - janes sinaga; Juita Lusiana Sinambela; Stimson Hutagalung; Rolyana Ferinia (JURNAL KADESI, 2021)
In this modern era, children are no longer involved in the daily tasks of the household, so it seems that they tend to be lazy. Parents have a role and responsibility to educate and familiarize their children to be involved in household chores every day at home, where if this is done it can educate children to have good character, be diligent, disciplined and responsible for now and in the future. Often parents do not involve them in household work because these children are focused on general science education but forget that character and responsibility education are also important. Parents also don't involve them, maybe because nowadays there are housemaids who do it. However, through this paper the author examines the negative consequences if parents do not involve them in household chores. The research method used is a qualitative method through library books, observations and experiences as parents. Through this paper, many parents will bias their children to be involved in household chores even for simple things.